Complications and outcome after rib fracture fixation: A systematic review. Issue 2 (August 2020) - Peek, Jesse; Beks, Reinier B.; Hietbrink, Falco; Heng, Marilyn; De Jong, Mirjam B.; Beeres, Frank J.P.; Leenen, Loek P.H.; Groenwold, Rolf H.H.; Houwert, R. Marijn
Abstract : BACKGROUND: In recent years, there has been a growing interest in operative treatment for multiple rib fractures and flail chest. However, to date, there is no comprehensive study that extensively focused on the incidence of complications associated with rib fracture fixation. Furthermore, there is insufficient knowledge about the short- and long-term outcomes after rib fracture fixation. METHODS: This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. The MEDLINE, EMBASE, and Cochrane databases were searched to identify studies reporting on complications and/or outcome of surgical treatment after rib fractures. Complications were subdivided into (1) surgery- and implant-related complications, (2) bone-healing complications, (3) pulmonary complications, and (4) mortality. RESULTS: Forty-eight studies were included, with information about 1, 952 patients who received rib fracture fixation because of flail chest or multiple rib fractures. The overall risk of surgery- and implant-related complications was 10.3%, with wound infection in 2.2% and fracture-related infection in 1.3% of patients. Symptomatic nonunion was a relatively uncommon complication after rib fixation (1.3%). Pulmonary complications were found in 30.9% of patients, and the overall mortality was 2.9%, of which one third appeared to be the result of the thoracic injuries and none directly related to the surgical procedure. The most frequently used questionnaire to assess patient quality of life was the EuroQol-5D (EQ-5D) (n = 4). Four studies reporting on the EQ-5D had a weighted mean EQ-5D index of 0.80 indicating good quality of life after rib fracture fixation. CONCLUSION: Surgical fixation can be considered as a safe procedure with a considerably low complication risk and satisfactory long-term outcomes, with surgery- and implant-related complications in approximately 10% of the patients. However, the clinically most relevant complications such as infections occur infrequently, and the number of complications requiring immediate (surgical) treatment is low. LEVEL OF EVIDENCE: Systematic Review, level III. Abstract : Supplemental digital content is available in the text.